2008
DOI: 10.1007/s11920-008-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Limbic changes identified by imaging in bipolar patients

Abstract: The hippocampus and amygdala are key limbic regions for memory formation and emotion modulation that are potentially involved in the cognitive and affective symptoms of bipolar disorder. Here we discuss the most consistent MRI literature in bipolar disorder, focusing on the role of the hippocampus and amygdala. In child and adolescent patients, a unique pattern of abnormalities has begun to emerge, with volume deficits in the hippocampus and amygdala already detectable early in the illness course. In adults, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 59 publications
(69 reference statements)
3
19
1
Order By: Relevance
“…Nevertheless, the findings of cross-sectional structural MRI studies in children and youths have been controversial. Whereas some studies have identified HCV decreases in young patients with BP [9,10,11], others found no differences in global HCV between children with BP and controls [12,13,14]. Our results suggest that youths with BP may exhibit a later development of the HC structures with continued decreases over time with a longer exposure to the illness.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Nevertheless, the findings of cross-sectional structural MRI studies in children and youths have been controversial. Whereas some studies have identified HCV decreases in young patients with BP [9,10,11], others found no differences in global HCV between children with BP and controls [12,13,14]. Our results suggest that youths with BP may exhibit a later development of the HC structures with continued decreases over time with a longer exposure to the illness.…”
Section: Discussioncontrasting
confidence: 68%
“…Interestingly, although most studies of adults with BP found no decreases in hippocampal volume (HCV) [7,8], the results from studies of children and adolescents have been controversial. Some studies have identified HCV decreases in young patients with BP [9,10,11]. In contrast, some of these studies found no differences in global HCV between children with BP and controls [12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In keeping with the literature, no evidence of hippocampal volume change was found in the BD patients (see Brambilla et al (2008) for review and Kempton and colleagues and Arnone and colleagues for meta-analyses (Arnone et al 2009;Kempton et al 2008)). The amygdala however showed some evidence of bilateral structural enlargement in BD patients reaching significance for the right.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast to SCZ, recent reviews and meta-analyses of imaging studies in BD find little indication of volumetric change in the hippocampus or amygdala (Arnone et al 2009;Brambilla et al 2008;Frey et al 2007;Kempton et al 2008;Killgore et al 2009;Ng et al 2009), although a few studies highlighting bipolar 'affective psychosis' groups have reported reduced hippocampal volume (Blumberg et al 2003;Strasser et al 2005;Velakoulis et al 1999). Moorhead et al (2007) have shown evidence of accelerated gray matter loss in BD compared to healthy individuals after illness onset and regions affected included the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Abe and colleagues reported significant gray matter volume reduction in MDD patients compared with controls in several brain regions, such as hippocampus (Abe et al 2010). More detailed evidence can be seen in the following reviews (Bora et al 2009;Brambilla et al 2008;Brunet-Gouet and Decety 2006;Konarski et al 2008). Several studies have suggested that Magel2 gene (MAGEL2) might be a susceptibility gene for Pradar-Willie syndrome (Bischof et al 2007;Kanber et al 2009).…”
Section: Introductionmentioning
confidence: 98%